The Effectiveness of Painting Therapy on Meaning in Life and Mental Health in Female Student with Low Academic Achievement - Hasan Ali Veiskarami; Leila Mansouri; Somayeh Roshanniya (Faṣlnāmah-i Farhang Mushavirah va Ravān/Darmānī, 2017)
The purpose of this study was to investigate the effectiveness of painting therapy on increasing meaning in life and mental health in female students with low academic achievement. The present semi experimental study included pre-test, post-test with the control group design. The statistical population of this study consisted of all female second grade students of guidance schools in Khoramabad city in the academic year of 2015-2016. Then 30 people with low academic achevement were selected through random multi stage cluster sampling and were assigned randomly to experimental and control groups. The instruments used in this study were meaning in life (Steger & etal, 2006) and mental health questionnaires (Goldberg, 1972). The experimental group received painting therapy for eight 60-minutes sessions, two sessions in a week lasting for one month. Analysis of the data was done using descriptive (average & standard deviation) and inferential (multiple covariance analysis) tests. Experimental group showed significant increase in mening in life and mental health after being trained. Based on the result we can say that painting therapy is an important method in improving meaning in life and mental gealth of students with low academic achievement.